From research to a political commitment to strengthen access to surgical, obstetric, and anesthesia care in Africa by 2030 - M'pele, Pierre; Seyi-Olajide, Justina O.; Elongo, Tarcisse; Lemvik, Jorn; Dovlo, Delanyo; Ameh, Emmanuel A. (Frontiers in Public Health, 2023)
Objective: To engage African leaders and key stakeholders to commit themselves towards the strengthening of surgical, obstetric and anesthesia care systems by 2030 in Africa. Methods: From research to a political commitment, a baseline assessment was performed to foster the identification of the gaps in surgical care as a first step of an inclusive process. The preliminary findings were discussed during the International Symposium on Surgical Obstetric and Anesthesia Systems Strengthening by 2030 in Africa. The conclusions served to draft the Dakar Declaration and its Regional Action Plan 2022-2030 to improving access to surgical care by 2030 in Africa and then endorsed by Heads of State. Results: The International Symposium was composed of two meetings that gathered (i) 85 Scientific Experts and (ii) 28 Ministers of Health or representatives from 28 sub-Saharan African countries. The 28 African countries represent: (i) in terms of population, 51% of the total population of the continent, (ii) 68% of the 47 African countries of WHO Africa Region, (iii) 58% of all countries (55) of the Africa Union and (vi) 79% (3371) health districts of the total (4271) of the health district of the WHO Africa Region. The International Symposium and the Heads of State summit successfully produced the Dakar Declaration on access to equitable, affordable, and quality Surgical, Obstetric and Anesthesia Care by 2030 in Africa and its Regional Actions Plan 2022-2030 which prioritizes twelve (12) urgent actions needed to be implemented, six (6) strategic priorities, sixteen (16) key indicators and an annual dashboard to monitor progress. Conclusion: The Dakar Declaration and its Regional Action Plan 2022-2030 is a commitment as a clear pathway to build quality and sustainable surgical, obstetric and anesthesia care in each African country within the ambitious framework of « The Africa we want » Agenda 2063[13].